2021
DOI: 10.1111/jopr.13456
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Reduction Depths of Tooth Preparation for Porcelain Laminate Veneers Assisted by Different Tooth Preparation Guides: An In Vitro Study

Abstract: Purpose: To evaluate the accuracy (trueness and precision) of reduction depths of guided veneer preparation assisted by four tooth preparation guides. Materials and Methods: Fifty resin artificial teeth were randomly divided into five groups (n = 10): a freehand group (F), silicone guide group (S), thermoplastic guide group (T), 3D printed uniform guide group (D), and 3D printed auto-stop guide group (A). A preparation for a window veneer on the maxillary right central incisor was performed by two surgeons who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
13
0
3
Order By: Relevance
“…Therefore, thermoplastic guides could provide more stable measurement points, and deviations caused by manual trial restoration are avoided [34]. The deviation of the preparation depth in this study was higher than the previously reported depths of 0.09 ~ 0.11 mm [19], which may be because the insufficient trimming of the prereduction region affected the fit of the thermoplastic guide.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Therefore, thermoplastic guides could provide more stable measurement points, and deviations caused by manual trial restoration are avoided [34]. The deviation of the preparation depth in this study was higher than the previously reported depths of 0.09 ~ 0.11 mm [19], which may be because the insufficient trimming of the prereduction region affected the fit of the thermoplastic guide.…”
Section: Discussionmentioning
confidence: 51%
“…The freehand preparation provided inconsistent accuracy with MADs of 0.237 mm, which was higher than that reported in a previous study [19]. This was possible because space evaluation was more complicated when the TRS contour differed from the original tooth.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Another study evaluated tooth reduction for veneer preparation on the cervical third, middle third, and incisal thirds of maxillary central incisors using freehand preparation, a silicone guide, a thermoplastic guide, 3D printing with a uniform guide, and 3D printing with auto-stop features. The results showed that freehand resulted in significantly more tooth reduction in all thirds prepared, while both types of 3D printed guides offered the least amount of tooth reduction and the most accurate preparation [27]. The two types of 3D guides can be classified as a 3D printed uniform and 3D printing with auto-stop.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, freehand techniques may be employed by experienced clinicians capable of visualizing the amount of tooth removal and space needed for the ceramic veneer without any reference. A recent study evaluated the free-hand, silicone guide, thermoplastic guide, and two different types of 3D printed tooth reduction guides and concluded that any type of tooth reduction guide provided more accuracy for veneer preparation than freehand preparation [27]. Therefore, it can be suggested that tooth reduction should be performed with a reduction aid in order to guarantee a controlled tooth reduction.…”
Section: Introductionmentioning
confidence: 99%